Chemical Composition, Bioactive Components and Antioxidant Activities from Root, Bark and Leaf Lindur - Siluh Putu Sri Dia; N. Nurjanah; Agoes Mardiono Jacoeb (Jurnal Pengolahan Hasil Perikanan Indonesia, 2015)
Plants lindur (Bruguiera gymnorrhiza) is one of the plants that have a potential asa source of bioactive compounds for the antioxidant. This study aimed to determine thechemical composition, bioactive compound and determine antioxidant activity of leaves,bark and roots of plants lindur (B. gymnorrhiza). This research was conducted throughseveral stages proximate test, stratified extraction, phytochemical test, and antioxidantactivity test with DPPH. The highest yield value resulting by ethanol extract of the leavesis 12,85 % and the lowest was produced by n-hexane root extract that is 0,18 %. The leavescontain high levels of protein, fat, and water which is the higher of the two parts from theother samples. Bark containing ash content (4,12%) and carbohydrates (46,02%). Root hasthe highest levels of carbohydrates that is 25,91 %. Bioactive components were detected onethanol and ethyl acetate extracts of the leaves are flavonoids, tannins, phenols, saponins,steroids and tritepenoid. Bark extract ethanol, ethyl acetate and ethanol root bark hasbioactive components there are flavonoids, tannins, phenols, saponins, and tritepenoid. Ethyl acetate extract of the roots only have bioactive components there are flavonoids,phenols, saponins, and triterpenoids. The potential antioxidant activity produced fromethyl acetate extracts of bark lindur with IC50 values is 14,21 ppm.Keywords: Antioxidants, phytochemicals, roots, ethanol, Bruguiera gymnorrhiza